Motivation, HR Skills, and Commitment: What Drives Employee Performance? - Muhammad Ilyas Alfarizi; Suhendra (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study explores how motivation and human resource (HR) competence influence employee performance, with organizational commitment acting as a mediating variable. Using a quantitative method, questionnaires were distributed to all 59 permanent employees at PT. Indopangan Sentosa. The data were analyzed using path analysis in SPSS. Results show that motivation has a strong, positive effect on organizational commitment and employee performance. HR competence, while not significantly related to commitment, does have a direct impact on performance. Organizational commitment also plays a key role in improving performance. Overall, motivation, competence, and commitment together contribute significantly to employee performance.